Five Year Financial Plan for New Ping Ping Lechon and Restaurant Inc - Danas,Janine Alyssa F.; Bernardo, Ma. Paula G.; Pili, Sarah Mae Q.; Benedicto, Ralph O.; De Vera, Emie Veatriz C.; Feliza, Jennilyn L.; Formoso, Fate Celynne R.; Sobrevinas, Frederick Douglas O.; Soriano, Chrizelle Anne V. and Villegas, Jeun FritzGerard C. 4 0 16; 5
EXECUTIVE SUMMARY: This study is designed to create a financial plan of New Ping Ping Lechon and Restaurant Inc. The financial problem is mainly focused on the entity's assets are underutilized in generating profit. The analysts used a five - year audited financial statements of the entity from 2012 - 2016 to make a financial analysis of the entity's problem. After carefully studying both internal and external environment of the entity, the financial ratios and historical data of the entity through their financial statements the analysis come up to have three alternative courses of action. These are Branch Out, Investment on Money Market Instruments, and Engaging in Food Cart Business. Among these three courses of action, the analysts decided that Branch Out is the best suited course of action to implement based on the financial problems they have in the entity. With the use of forecasted financial statements of the entity, the analysts projected the financial statements of the entity after employing the selected couse of action. The course of action used by the analysts was able to increase profit of the entity by 125%, in the 5-year span.
Financial Planning: (BSBA Major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2